A flexible way to study composites in ecology using structural equation modeling - Yu, Xi (2025)
Yu, X., Schuberth, F., & Henseler, J. (2025). A flexible way to study composites in ecology using structural equation modeling. Scientific Reports, 15, 1-16. Article 4597. https://doi.org/10.1038/s41598-025-88675-0 --- The authors thank Alexandra Elbakyan for her efforts to make science accessible. Jörg Henseler: acknowledges financial support from FCT Fundação para a Ciência e a Tecnologia (Portugal), national funding through a research grant from the Information Management Research Center - MagIC/NOVA IMS (UIDB/04152/2020).